1977
DOI: 10.1159/000158123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid and its 2-Sulfate on Rabbit Aortic Intimal Thickening

Abstract: Effects of intravenously injected L-ascorbic acid or L-ascorbic acid 2-sulfate on aortic intimal thickening were examined histologically, qualitatively, and quantitatively in the upper, middle and lower thoracic aortic positions of cholesterol-induced atherosclerotic rabbits. A means of evaluating the degree of pathology of the aortic positions was developed employing five descriptive statistics of intimal thickening. Both L-ascorbic acid and L-ascorbic acid 2-sulfate inhibited intimal thickening. The most sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Therefore, the higher spe cific activity o f C 4 -S in nonsupplemented animals suggests increased degradation o fC-4-S, with concomitant increased de novo synthesis. These observations may be part of the reduced intimal thickening mechanism reported by Verlangieri et aL (21) previously. Changes in G A G turnover may have a profound effect on maintaining the structural and permeability characteristics o f the intima and result in a reduced rate o f atherogenesis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, the higher spe cific activity o f C 4 -S in nonsupplemented animals suggests increased degradation o fC-4-S, with concomitant increased de novo synthesis. These observations may be part of the reduced intimal thickening mechanism reported by Verlangieri et aL (21) previously. Changes in G A G turnover may have a profound effect on maintaining the structural and permeability characteristics o f the intima and result in a reduced rate o f atherogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…The remaining piece o f aorta was divided in half. The half originally most proximate to the bifurcation was designated the middle section, the distal remaining piece the lower section as described by Verlangieri et al (21). The upper and lower sections were frozen immediately at 10 °C for further analysis.…”
Section: A Nimal Proceduresmentioning
confidence: 99%
“…Ascorbate can increase the oxidation, however, of partially oxidized LDL [29,30]. Some studies have shown an anti-atherogenic effect of ascorbate in cholesterol fed-rabbits [33,34], but others have demonstrated that ascorbate had no protective effect in these animals [35]. Similarly to a-tocopherol, there is no strong evidence that ascorbate decreases cardiovascular disease in clinical trials [8,9,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate supplementation of cholesterol-fed animals has been shown to be anti-atherogenic [15][16][17], although other studies have reported no significant biological effect [18,19]. Some epidemiological studies in man [20,21], but not all [22], have shown that individuals who consume high concentrations of ascorbate through diet or supplements tend to have lower risks of cardiovascular disease, however, large clinical trials have found no benefits of antioxidant supplementation on cardiovascular disease risk [23].…”
Section: Introductionmentioning
confidence: 99%